No Price Like Home: Global House Prices, 1870-2012 - Thomas Steger; Katharina Knoll; Moritz Schularick (ZBW - Deutsche Zentralbibliothek für Wirtschaftswissenschaften, Leibniz-Informationszentrum Wirtschaft, 2015)
How have house prices evolved in the long-run? This paper presents, for the first time, annual house prices for 14 advanced economies since 1870. Based on extensive data collection, we show that the past decades have seen a historically unprecedented boom in global house prices. Real house prices in most industrial economies stayed constant from the 19th to the mid-20th century, but rose strongly during the second half of the 20th century. Land prices, not replacement costs, hold the key to understanding the trajectory of house prices in the long-run. Rising land prices explain about 80 percent of the global house price surge since World War II. In the past 30 years alone, land prices in advanced economies approximately doubled in real terms. We also show that gains in the value of land have been the key driver of the increasing wealth-to-income ratios in advanced economies over the past decades.
Keywords: N10; O10; R30; 330